Dopamine or biopterin deficiency potentiates phosphorylation at (40)Ser and ubiquitination of tyrosine hydroxylase to be degraded by the ubiquitin proteasome system - Kawahata, Ichiro; Ohtaku, Shiori; Tomioka, Yoshihisa; Ichinose, Hiroshi; Yamakuni, Tohru (Biochemical and biophysical research communications, 2015)
The protein amount of tyrosine hydroxylase (TH), that is the rate-limiting enzyme for the biosynthesis of dopamine (DA), should be tightly regulated, whereas its degradation pathway is largely unknown. In this study, we analyzed how the TH protein is chemically modified and subsequently degraded under deficiencies of DA and tetrahydrobiopterin (BH4), a cofactor for TH, by using pharmacological agents in PC12D cells and cultured mesencephalic neurons. When inhibition of DA- or BH4-synthesizing enzymes greatly reduced the DA contents in PC12D cells, a marked and persistent increase in phosphorylated TH at (40)Ser (p40-TH) was concomitantly observed. This phosphorylation was mediated by D2 dopamine auto-receptor and cAMP-dependent protein kinase (PKA). Our immunoprecipitation experiments showed that the increase in the p40-TH level was accompanied with its poly-ubiquitination. Treatment of PC12D cells with cycloheximide showed that total-TH protein level was reduced by the DA- or BH4-depletion. Notably, this reduction in the total-TH protein level was sensitive not only to a 26S proteasomal inhibitor, MG-132, but also to a PKA inhibitor, H-89. These data demonstrated that DA deficiency should induce compensatory activation of TH via phosphorylation at (40)Ser through D2-autoreceptor and PKA-mediated pathways, which in turn give a rise to its degradation through an ubiquitin-proteasome pathway, resulting in a negative spiral of DA production when DA deficiency persists.